Providing A Personalized Healthcare Service To The Patients Using AIOPs Monitoring - Ajay Reddy Yeruva (Eduvest - Journal of Universal Studies, 2023)
We see the critical role technology plays in healthcare in the midst of a continuous worldwide health crisis. To combat the epidemic, South Korea, for example, used smart city' technology and government-developed applications that follow individuals in quarantine. A biosensor that can identify the virus in saliva samples has just been created by India's National Institute of Animal Biotechnology, Hyderabad. These developments are made feasible by the usage of certain biosensors that have printed circuit boards with metal core components capable of withstanding large variations in moisture and temperature. A very sophisticated breakthrough, artificial intelligence for IT operations, is altering the healthcare sector in addition to the technology that aid nations in combating the epidemic. This general phrase, also known as AIOps, describes the automated detection and repair of typical IT problems using big data, machine learning, and other AI technologies. AIOps may be used in the healthcare industry to teach computers to analyse CT scan pictures, follow the progression of various illnesses, assess the effectiveness of patient therapy, and much moren.